《西游记女儿国》电影中使用的言语行为分析 PENGGUNAAN TINDAK TUTUR PADA FILM THE MONKEY KING 3 - Karina karina; Wesley Kuandinata (Journal of Language, Literature and Teaching, 2022)
The study aims to describe the types of illocutionary speech acts and social factors of illocutionary speech acts in the film The Monkey King 3. Using qualitative descriptive research design and source of the data is the movie The Monkey King 3. Using documentation technique and the data analysis technique used consists of three stages, namely: data condensation, data presentation and drawing conclusions and induction techniques. Based on the results of data analysis are 22 illocutionary speech acts on love-topic communication and 14 illocutionary speech acts on hate-topic communication. The types of direct illocutionary speech acts in communication with the topic of love are 18 direct speeches and 4 indirect speech acts. Meanwhile, the types of indirect illocutionary speech acts in hate-topic communication are 12 indirect utterances and 2 indirect utterances. Factors that influence the use of speech acts in communication with the topic of love in the film The Monkey King 3 are the participant factors of 3 utterances; background factor 3 utterances; topic factor 8 utterances; function factor 8 utterances. Meanwhile, the factors that influence the use of speech acts in hate-topic communication in the film The Monkey King 3 are the participant factors of 5 utterances; background factor 1 speech; topic factor 2 speech; function factor 6 speech.Key Words: Pragmatics, Speech Acts, Social Factor, Love-Hate,                     The Monkey King 3